In vitro effects of nonesterified fatty acids and β-hydroxybutyric acid on inflammatory cytokine expression in bovine peripheral blood leukocytes - Li, Cheng-Yan; Liao, Yu-Wen; Liu, Chia-So; Cheng, Chuen-Yu; Chan, Jacky Peng-Wen; Wang, Chien-Kai (Italian journal of animal science, 2021)
Negative energy balance (NEB) occurs in dairy cows during the transition period, during which time the blood concentrations of nonesterified fatty acids (NEFA) and metabolic ketones such as β-hydroxybutyric acid (BHBA) are elevated. These increased levels may disrupt immune functions and are regarded as risk factors associated with postparturient inflammatory disorders. Therefore, the aim of this study was to investigate the effects of NEFAs and BHBA on inflammatory cytokine expression in bovine peripheral leukocytes in vitro. Peripheral blood mononuclear cells (PBMCs) and peripheral polymorphonuclear leukocytes (PMNLs) were collected from 16 Holstein cows and treated for 4 h with NEFA (0.1, 0.6, and 1.5 mM) or BHBA (5 and 10 mM), alone or combination with lipopolysaccharides (LPS, 1 µg/mL). The expression levels of the inflammatory cytokines TNF-α, IL-1β, IL-6, IL-8, and IL-10 were then determined. The results indicated that PBMCs and PMNLs responded to NEFA but tolerated BHBA. NEFA treatment dose-dependently induced the expression of TNF-α, IL-1β, IL-8, and IL-10 in PBMCs and that of IL-1β, IL-6, IL-8, and IL-10 in PMNLs. Combination treatment of LPS with NEFA further increased the levels of IL-10 expression in PBMCs and IL-1β and IL-6 expression in PMNLs. Taken together, these findings suggest that NEFA and BHBA enhance the expression of inflammatory cytokines in PBMCs and PMNLs and may disrupt the immune regulation of peripheral leukocytes, leading to an increased risk of inflammatory disorders. Preventing increases in blood NEFA concentration may thus help to reduce the risk of inflammatory disorders in dairy cows during the transition period. Highlights In cows with NEB, during the transition period, NEFA but not BHBA induced proinflammatory cytokine expression in PBMCs and PMNLs. NEFA enhanced LPS-induced proinflammatory cytokine expression in both PBMCs and PMNLs.